2012
DOI: 10.1186/1471-2164-13-s4-s5
|View full text |Cite
|
Sign up to set email alerts
|

On the effect of protein conformation diversity in discriminating among neutral and disease related single amino acid substitutions

Abstract: BackgroundNon-synonymous coding SNPs (nsSNPs) that are associated to disease can also be related with alterations in protein stability. Computational methods are available to predict the effect of single amino acid substitutions (SASs) on protein stability based on a single folded structure. However, the native state of a protein is not unique and it is better represented by the ensemble of its conformers in dynamic equilibrium. The maintenance of the ensemble is essential for protein function. In this work we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…In terms of changes in structure stability, it was previously found in FoldX calculations (Juritz et al, 2012) that the best discrimination cutoff for G values between polymorphic and disease-associated SASs was ±2 kcal/mol. Taking these values into account, we classified SASs as stabilizing for those with a G ࣙ 2 kcal/mol, destabilizing for those below (−2 kcal/mol), and neutral for those with values in between.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of changes in structure stability, it was previously found in FoldX calculations (Juritz et al, 2012) that the best discrimination cutoff for G values between polymorphic and disease-associated SASs was ±2 kcal/mol. Taking these values into account, we classified SASs as stabilizing for those with a G ࣙ 2 kcal/mol, destabilizing for those below (−2 kcal/mol), and neutral for those with values in between.…”
Section: Resultsmentioning
confidence: 99%
“…As a protein's native state is better represented by an ensemble of conformers, the effect of SASs should be evaluated on each of the available conformers of the protein. Following this approach, we found that the damaging effect of SASs on protein function evaluated in different conformations could help in the understanding of disease associated SASs (Juritz et al, 2012). For this reason, and to obtain a mechanistic analysis of the SAS effect, we explicitly studied the described SASs with regards to the conformational diversity of the EGFR protein.…”
Section: Introductionmentioning
confidence: 99%
“…). Conformational diversity is a key concept to understand many processes and mechanisms in protein function, such as enzyme catalysis, promiscuity in protein interactions, protein‐protein recognition, signal transduction, mechanisms of disease‐related mutations, immune escape, the origin of neurodegenerative diseases, protein evolutionary rates, conformer‐specific substitution patterns, the origins of new biological functions, molecular motors, and co‐evolutionary measurements between residues (for a recent review please see). Furthermore, we have recently shown that the distribution of CD in a large dataset of proteins, with experimentally determined CD (approximately 5000 proteins), results in three main groups of proteins with different structure‐function relationships .…”
Section: Discussionmentioning
confidence: 99%
“…First, we found that the extent of the CD could be as large as the MSD (Fig 1). Conformational diversity is a key concept to understand many processes and mechanisms in protein function, such as enzyme catalysis [49], promiscuity in protein interactions [50], protein-protein recognition [51], signal transduction [52], mechanisms of disease-related mutations [53], immune escape [54], the origin of neurodegenerative diseases [55], protein evolutionary rates [56], conformer-specific substitution patterns [57], the origins of new biological functions [58], molecular motors [59], and co-evolutionary measurements between residues [24,60] (for a recent review please see [17]).…”
Section: Discussionmentioning
confidence: 99%